Development of STEAM-Based Learning with a Deep Learning Approach to Enhance Critical Thinking Skills on Circle Material - Lutfiana Ramadani; Abi Suwito; Susanto Susanto; Arika Indah Kristiana; Frenza Fairuz Firmansyah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study aims to develop STEAM-based mathematics learning tools integrated with a deep learning approach to enhance junior high school students’ critical thinking skills on circle material. The study employed the 4D development model consisting of Define, Design, Develop, and Disseminate stages. The developed products included a Module Implementation Plan (RPM), teaching materials, interactive learning media, Student Worksheets (LKM), and critical thinking assessment instruments. The novelty of this study lies in the systematic integration of STEAM principles and deep learning into all learning components specifically designed for circle material at the junior high school level. The validity of the tools was assessed by expert validators, while practicality was evaluated through observations of learning implementation, student activities, and student responses. Effectiveness was examined using the N-Gain test. The results showed that the developed tools were valid (mean score = 3.76), practical, and effective, with students demonstrating active participation, positive responses, and a moderate improvement in critical thinking skills (N-Gain = 0.60).